The Effects of Price Perception, Menu Variety, and Taste on Satisfaction and Repurchase Intention - Rahayu Lestari; Resti Hardini (Penerbit Goodwood, 2026)
Purpose: This study aims to analyze the influence of price perception, menu variation, and taste on customer satisfaction and repurchase intention among consumers at South Tangerang Snack Park.Metodhology: This research used a quantitative approach method with primary data collected by questionnaires distributed to 95 consumers. The data selected by using purposive sampling and the data analyzed by using Partial Least Squares with SmartPLS 3.0.Result: The findings show that price perception, menu variation, and taste show significant effect and positive on customer satisfaction. Customer satisfaction also contributes to consumers’ intention to repurchase. However, menu variation does not directly influence repurchase intentionConclusions: Consumer satisfaction is an important factor in encouraging repeat purchases. Fair price perception and good taste can strengthen satisfaction and increase consumers’ willingness to buy againLimitations: This study is limited to consumers of South Tangerang Snack Park, with only 95 respondents, restricting generalizability to broader culinary markets. The small sample size, single location focus, and specific timeframe may not fully represent diverse consumer behaviors, seasonal fluctuations, or regional differences across other culinary destinations in Indonesia.Contributions: This study provides practical insights for culinary business owners to improve customer satisfaction and loyalty by optimizing price perception, menu variation, and taste quality to strengthen competitiveness and repurchase intention.